Synthesis of Novel bis‐Triazolinedione Crosslinked Amphiphilic Polypept(o)ide Nanostructures. Issue 11 (25th April 2019) - Brannigan, Ruairí P.; Kimmins, Scott D.; Bobbi, Elena; Caulfield, Séamus; Heise, Andreas
Abstract: Owing to their wide range of inherent functionality, hydrolytic stability, biodegradability, and low toxicity, polypeptide‐based materials have been increasingly exploited for controlled drug release applications. More recently, the incorporation of poly(α‐peptoid)s such as poly(sarcosine) into polypeptide‐based materials has been investigated owing to their potential as naturally derived "stealth polymers." Here the synthesis of novel amphiphilic polypept(o)ide nanoparticles is described utilizing silica templates as a macroinitiator for the ring‐opening copolymerization ofl ‐tryptophan andd /l ‐phenylalanine NCAs and subsequent chain extension with sarcosine NCA. These particles are subsequently crosslinked utilizing the TAD‐indole "click" chemistry and the silica templates are eroded via treatment with HF yielding core crosslinked amphiphilic polypept(o)ide nanostructures. This synthetic strategy offers a unique platform to yield naturally‐derived degradable core‐crosslinked nanostructures, which may have the potential to be utilized in the future as delivery vehicles for hydrophobic small molecules. Abstract : Core‐crosslinked amphiphilic polypept(o)ide nanoparticles are synthesized utilizing N‐carboxyanhydride ring‐opening polymerization (NCA‐ROP), initiated from a silica template, and crosslinked utilizing TAD‐indole click chemistries. Subsequently the silica template is removed to yield naturally‐derived degradable nanostructures.